New Cretaceous lungfishes (Dipnoi, Ceratodontidae) from western North America. (28th November 2016) - Frederickson, Joseph A.; Cifelli, Richard L.
Abstract: Ceratodontid lungfishes are generally rare, poorly represented elements of North America's Mesozoic ecosystems, with previously known maximum diversity in the Late Jurassic. Herein we describe four new species of the form genus Ceratodus, from the Cretaceous of the Western Interior, considerably expanding fossil representation of post-Triassic dipnoans in North America. To model taxonomic and morphologic diversity, we adopt a four-fold system of phenetically based species groups, named for exemplars from the Morrison Formation. Ceratodus kirklandi n. sp. ( Potamoceratodus guentheri group) and C . kempae n. sp. ( C . frazieri group) represent a hitherto unsampled time interval, the Valanginian. Ceratodus nirumbee n. sp. and C . molossus n. sp. extend the temporal ranges of the C . fossanovum and C . robustus groups upward to the Albian and Cenomanian, respectively. These new occurrences show that ceratodontids maintained their highest diversity from the Late Jurassic through the mid-Cretaceous (Albian–Cenomanian), an interval of ~60 Myr. The existing record suggests that some of the later (mid-Cretaceous) ceratodontids may have been tolerant of salt water; to date, there is no evidence that they aestivated. Only a few occurrences are known from horizons younger than Cenomanian. Demise of ceratodontids appears to be part of a broader pattern of turnover that occurred at the Cenomanian-Turonian boundary in North America.